(untitled) (Gaceta Técnica, 2021)
This is an overview of the book Analysis of Structures with Dynamic Loads of the PhD. Luis Edgardo Suárez, professor at the department of civil engineering and surveying at the University of Puerto Rico, Mayagüez campus, whose publication was made in 2014. The most important aspects, concepts and procedures within the field of structure dynamics, which will serve as a solid foundation for both undergraduate and graduate level readers. Several of the topics addressed throughout the text include basic and easy-to-understand aspects since, in turn, many details and examples are presented that consolidate the learning even of certain readers who are unaware of a specific topic